Tech-Based Psychosocial Mentoring Innovation for Teachers in Remote Schools: Enhancing Mental Well-Being and Professionalism - sunarsih, Sunarsih; Aktar, Salim; Arifin, Arifin; Br Barus, Depitaria; Astri Tarigan, Beby; Clara Abbiati, Aqila; Gokma Uli Alicia, Winda (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Teachers in remote schools often experience psychological stress and professional burnout due to limited resources, heavy workloads, and lack of psychosocial support, which negatively affect both teacher well-being and learning quality. This community service program aims to enhance teachers’ mental well-being and professionalism through a Tech-Based Psychosocial Mentoring Innovation, supporting SDGs 3, 4, and 8, as well as University Key Performance Indicators (IKU) 3 and 7 by empowering educators in low-resource settings. The program was implemented in three stages: preparation (needs assessment, development of the “Healthy Teacher” psychosocial module, and creation of a Google Site–based Learning Management System), implementation (three-day training on stress management, emotional regulation, and reflective mentoring), and evaluation (using the WHO-5 Wellbeing Index, daily reflections, and focus group discussions). Results showed a significant improvement in teachers’ well-being, with WHO-5 scores increasing from moderate to good levels. Teachers also reported improved stress management, higher motivation, and stronger collegial support. The program produced ten psychoeducational videos, a digital LMS, and a sustainable reflective teacher community supported by two internal mentors. Overall, this innovation effectively enhanced teachers’ psychological well-being and professionalism in remote schools and can be replicated in other rural or low-resource educational settings to promote sustainable teacher well-being and school quality improvement.